In-service EFL teachers’ perceptions on university training regarding teaching mixed-ability classes at USACH - Cabello Toro, Lissette (Universidad de Santiago de Chile, 2024)
Integrantes: Lissette Cabello Toro, Daniela Jara Molina, Daniela Palma Urrutia, Claudia Villalobos Araneda
Keywords: Profesores de inglés - Formación profesional Chile; Inglés - Enseñanza superior - Chile; Educación inclusiva - Chile